Frameworks backend para el desarrollo de la plataforma tecnológica de gestión de comunidades académicas y recreativas de la Universidad Técnica de Babahoyo. - Almeida Santillán, Oscar Adonis (2024)
Currently, backend frameworks have emerged as a popular solution to develop robust and scalable projects, providing a structure and a set of tools that streamline the application development process. In this context, given the complications present in the development process of the seed project ‘Technological platform for the management of academic and recreational communities of the Technical University of Babahoyo’, a solution has been sought through a proposed backend framework. As the platform grows in users and communities, the security of its data and the efficiency of the platform is a fundamental priority. This study not only addresses theoretical aspects of the technologies used in the platform and the backend frameworks, but also proposes a solution to be implemented. This research will contribute to the improvement of the technological platform in order to make it more efficient, secure and scalable to meet the needs of the university community in the future.